PENGEMBANGAN TES SUBJEKTIF BERBASIS HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI POLA BILANGAN - Asri Asri; Sukmawati Sukmawati; Wahyuddin Wahyuddin (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This research is to develop a subjective test instrument based on Higher Order Thinking Skills (HOTS) on number pattern. The research method used in this research is research and development (RD). This study uses the ADDIE model which consists of five stages: including analysis, design, development, implementation, and evaluation (Sugiyono, 2017). The results of the CVR test of 3 items showed that all questions met the appropriate criteria but were recommended for improvement. A total of 3 questions include material, construction, and language aspects. Then a limited field trial was conducted on 20 class VIII students of SMPN 2 Lembang. 3 valid questions used for wide field trials on 30 class VIII students of SMPN 2 Lembang. In the limited field test the reliability of the test is 0.615, while the broad field test reaches 0.642. Based on the discriminatory power, in the limited field test and the wide field test, the discriminatory power of the questions in both situations is quite good. Based on the level of difficulty in the limited field test questions, 3 moderate questions were found, while in the wide field test, 1 easy question and 2 medium questions.